Organizational routines and the possibilities for racial equity in test-optional admissions - Slay, Kelly E. (Frontiers in Education, 2025)
Test-optional admissions policies have been championed as a tool for mitigating the losses to racial diversity in the current racial and socio-political climate, but existing research suggests their impact on diversifying student enrollment is unclear. In this article, I suggest that eliminating test score requirements, while in theory may represent a critical step toward leveling the playing field in selective college admissions, this single policy change may be limited in its capacity to significantly advance racial equity and diversity if the organizational routines deeply embedded in the broader system of college admissions writ large, are left unexamined. Drawing from organizational routines and theory of racialized organizations as a conceptual lens, I review three categories of organizational routines critical to the implementation and use of test-optional admissions: (a) institutional priorities (b) admissions criteria and (c) evaluative processes. In doing so, I contribute to a small, but growing body of research that draws attention to the myriad ways race operates in the admissions process from a meso-level perspective—the first which explicitly examines undergraduate test-optional admissions. I highlight the multi-level nature of admissions and the possibilities of test-optional policies—both their promise and potential problems—for advancing racial equity.